Current Strategies to Reducing Interval Breast Cancers: A Systematic Review - Goh RSJ; Chong B; Yeo S; Neo SY; Ng QX; Goh SSN (Breast Cancer: Targets and Therapy)
Rachel Sze Jen Goh,1 Bryan Chong,1 Selvie Yeo,1 Shao Yun Neo,1 Qin Xiang Ng,2,* Serene Si Ning Goh1– 3,* 1NUS Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 2Saw Swee Hock School of Public Health, National University of Singapore and National University Health System, Singapore; 3Department of Surgery, National University Hospital Singapore, Singapore*These authors contributed equally to this workCorrespondence: Serene Si Ning Goh, Department of Surgery, National University Hospital, Singapore, Email serene_sn_goh@nuhs.edu.sgBackground: Interval breast cancers (IBCs) are detected between regular mammographic screenings after an initially negative result. Studies have shown that the prognosis of IBCs is similar to that of unscreened symptomatic cancers and is hence a surrogate used to assess the effectiveness of screening programs. This systematic review consolidates the current literature available on strategies to reduce the rates of IBC.Methods: Following PRISMA guidelines, three databases were searched from inception till October 29, 2023 to identify papers, which reported IBC rates. Key search terms included “interval breast cancer”, “mammogram”, “tomosynthesis” and “screening”.Results: A total of 32 articles were included. Fourteen studies discussed the use of digital breast tomosynthesis (DBT) as an alternative screening modality to mammograms. Six studies discussed the use of artificial intelligence (AI) on mammograms, five studies discussed the use of supplemental modalities including ultrasonography (US) in addition to mammograms, five studies discussed varying screening intervals and two studies discussed tamoxifen use.Conclusion: The trajectory of IBCs can be altered by early detection when they are more amenable to treatment, through advanced screening techniques, adjusting inter-screening intervals and modifiable risk factors. The goal is to create a screening protocol that is economically effective and accessible to various populations.Plain Language Summary: This study looked at ways to reduce interval breast cancers, which are cancers that appear between regular breast screening appointments after a previous scan showed no signs of cancer. These cancers are often more aggressive and harder to treat, so finding ways to detect them earlier is important. We reviewed 32 high-quality studies from around the world, covering over 5,500 cases of interval breast cancer, to understand which strategies work best. We found that using digital breast tomosynthesis (a 3D imaging method) generally reduced missed cancers compared to traditional mammograms, especially in women with dense breasts. Artificial intelligence tools also showed promise in helping radiologists detect cancers more accurately. Adding ultrasound to standard mammograms helped pick up cancers that mammograms alone might miss, particularly in women at higher risk. Shortening the time between screenings from every two years to annually was linked to lower rates of interval cancers. Some evidence also suggested that using tamoxifen, a hormone therapy that reduces breast density, may lower the risk of interval cancers. However, these strategies must be balanced with cost, accessibility, and the potential risks of overdiagnosis or unnecessary testing.Keywords: interval breast cancer, screening, mammogram, systematic review